XEROPHYTIC NANOCELLULOSE: A PLATFORM LINKING SMART DRUG DELIVERY, TISSUE ENGINEERING, AND SUSTAINABLE CONSTRUCTION - Roberto Ramos, Paulo; Almeida Ferreira, Rodrigo; Dourado Carvalho, Luzineide; de Almeida Araújo, Cleyton; Cordeiro Pereira, Sidclay; Frensch, Gustavo; Silva Carvalho, Rubens; Lemos Cavalcante de Carvalho Santiago, Beatriz; de Deus Cysneiros Cavalcanti, Airton; Mara Marinho da Silva, Lícia; Gomes de Lima, Carlos; Santana de Jesus, Mariana; et al. (Revista Gênero e Interdisciplinaridade, 2026)
The increasing demand for sustainable materials has intensified the search for alternatives to synthetic polymers, particularly in applications requiring both mechanical and biological performance. In this context, nanocellulose has emerged as a promising platform, although gaps remain in integrating its structural properties with multifunctional applications, especially when derived from xerophytic plants. This study aimed to analyze the physicochemical, mechanical, and biological properties of nanocellulose obtained from semi-arid adapted species, focusing on its applications in controlled drug delivery systems and sustainable construction materials. An integrative review was conducted between October 2025 and March 2026, using major scientific databases, yielding 315 initial records, of which 35 comprised the final corpus. The results indicate that high crystallinity, aspect ratio, and hydrophilicity enhance nanocellulose performance as a hydrogel matrix, a responsive drug delivery system, and a reinforcing agent in composites. The discussion highlights a functional convergence between molecular properties and applications, while also revealing disciplinary fragmentation and a lack of studies on Caatinga species. It is concluded that xerophytic nanocellulose represents a platform technology with significant innovation potential, particularly when integrated into sustainable production frameworks.